A further understanding on the strength development of cement pastes in the presence of triisopropanolamine used in CRTS III slab track. (10th January 2022) - Zhang, Yanrong; Zhang, Xuesong; Cai, Xiaopei; Gao, Liang; Li, Qiangqiang; Kong, Xiangming
Highlights: Effects of TIPA on strength, hydration, pore structure and hydrates' morphologies were studied. The mechanism of TIPA was elucidated based on a further understanding on hydration. TIPA heightens hydration degree because of triggering the reaction of C4 AF and C3 S. At low dosages, TIPA refines pore structure and significantly increases strength. At high dosages, increased harmful pores and changed morphologies of hydrates reduce late strength. Abstract: Accelerators are commonly used in the self-compacting concrete of CRTS III slab track to advance its strength development in cold areas. Triisopropanolamine (TIPA) is a known accelerator, and its influences on the strength development of hardened cement pastes (HCPs) were discussed based on a further understanding of cement hydration and microstructure. The results show that the addition of TIPA visibly heightens hydration degree at each age because it triggers the reaction of C4 AF and gently promotes C3 S hydration. At low dosages, more hydrates deposited in capillary pores facilitate a refined pore structure and therefore, significantly increase the early and late strengths. On the contrary, a high dosage of TIPA results in a loose and porous structure at an early age owing to the emergence of numerous AFm platelets and the reduction of Ca(OH)2 crystals, so that the heightened hydration degree only slightly increases the early compressive and flexural strengths. At a later age, high dosages of TIPA cause an increase in the volume of harmful pores (greater than 50 nm), which may result from the appearance of some pores full of fractional AFm and the changed morphology of Ca(OH)2 . Therefore, the late compressive strength of HCPs remains almost unchanged under the positive effect of the heightened hydration degree coupled with the negative effect of the increased volume of the harmful pores. In contrast, the late flexural strength sharply decreases, which is ascribed to both of the increased volume of the pores larger than 50 nm and the morphological changes of hydration products.